High-quality chromosome-level genome assembly of the whitespotted conger (Conger myriaster) - Shenglei Han; Chen Li; Shuo Li; Yan Chen; Chenggang Wang; Kaiqiang Liu; Yuyan Liu; Hong-Yan Wang; Qian Wang; Xuwen Cao; Bao Shi; Changwei Shao (Scientific Data)
Abstract The whitespotted conger (Conger myriaster) is an ecologically and economically significant benthic marine species widely distributed across East Asia’s coastal waters. Despite this importance, the genomic resources for this species remain limited, hindering evolutionary and aquaculture research. Here, we present the first high-quality chromosome-level genome assembly of C. myriaster using PacBio CLR, WGS, 10X Genomics and Hi-C data. The resulting 1.09 Gb genome assembly exhibits excellent contiguity, with 97.49% of sequences anchored onto 19 chromosomes. The assembled genome achieved a BUSCO completeness stands at 98.00%, containing 34.80% repetitive sequences and 24,063 predicted protein-coding genes. This foundational genomic resource overcomes a major limitation, providing the essential framework for future investigations into the evolutionary adaptations and for the genetic improvement of C. myriaster in aquaculture.